V2G Technology to Design a Smart Active Filter for Solar Power System - F. R. Islam; H. R. Pota (Institute of Advanced Engineering and Science, 2013)
This paper presents the implementation of Vehicle to Grid (V2G) technology for designing a shunt active filter to improve power quality of solar generation. A system model with solar generation and a dynamic model of PHEVs are introduced here based on third order battery model. A simple battery scheme is proposed for the control of the charging and discharging of the PHEVs using a power electronic interface. The active filter controller is designed based on the instantaneous power theory (p-q theory) to improve the wind generator performance through compensating the oscillating real and reactive power from PHEVs. Simulations have been carried out and demonstrate that PHEVs have the potential to work as active filter with solar power generator to improve power quality, dynamic power factor correction and harmonics current compensation.DOI: http://dx.doi.org/10.11591/ijpeds.v3i1.1711